Heritages in progress. Designing their regeneration - Blanc, Françoise (AGATHÓN | International Journal of Architecture, Art and Design, 2020)
To design with Heritage for the future within the complexity of its scales and its contemporary stakes opens an innovating field. The idea of ‘regeneration’ becomes a drive for project at all scales. The examination of this notion allows the introduction to the discourse, which is developed afterwards with the exposure of two meaningful experiments: they propose the current and future regeneration of Heritage within its large space context and open a new conceptual frame for the project. The case of Mont Saint Michel in France, a realized pilot project and the internationally collaborated academic works on the water supplies Heritage and the metropolitan sprawl in the territory of Jaipur-Amber, Rajasthan, illustrate the contribution to a founding reflection on the becoming of Heritages, seen as a renewable resource and innovative carrier.